An Optimal Control Economy Model of Investing in Three Industries for a Region and Some Properties. Issue 4 (March 2019) - Luo, Dongsheng; Liu, Yanmin; Wang, Changchun; Tang, Xiaoyan
Abstract: In this article, we first construct an optimal control mathematics model about economy investing in three industries in a region; then give the existence of the fastest and valid method of investing in three industries for a region; at last, we show that the fastest way to invest in three industries to obtain some target is to input the largest total amount of the capital all through the investing process.